2013
DOI: 10.1093/aje/kwt110
|View full text |Cite
|
Sign up to set email alerts
|

History of Infertility and Risk of Gestational Diabetes Mellitus: A Prospective Analysis of 40,773 Pregnancies

Abstract: Studies of delayed conception and risk of gestational diabetes (GDM) are sparse, although common underlying mechanisms are plausible, including insulin resistance and inflammation. The association between a history of infertility and GDM was assessed prospectively among 40,773 eligible pregnancies in the US Nurses' Health Study II cohort (1989-2001). Biennial questionnaires provided updated information on infertility and several lifestyle and health-related characteristics. Multivariable log-binomial models wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 41 publications
9
22
1
1
Order By: Relevance
“…Our findings are consistent with a previous analysis in the NHS II cohort of infertility and risk of gestational diabetes mellitus (GDM) in parous women [27]. Here, we found that prepregnancy infertility was associated with a 39% higher risk of GDM (RR 1.39 [95% CI 1.24, 1.57]).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with a previous analysis in the NHS II cohort of infertility and risk of gestational diabetes mellitus (GDM) in parous women [27]. Here, we found that prepregnancy infertility was associated with a 39% higher risk of GDM (RR 1.39 [95% CI 1.24, 1.57]).…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, tubal infertility could be an intermediate marker for STIs and inflammation which may increase risk of hypertension. In addition, we have previously found positive associations between infertility due to tubal disease and risk of other cardio-metabolic conditions including gestational diabetes (24) and type 2 diabetes (Tobias, under review for publication). However, we found no relation of tubal infertility to hypertension when using a comparison group of male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Closely spaced childbearing may reflect less breast feeding and less efficient use of contraception and be associated with other health behaviours and socioeconomic status. Very long intervals may be a consequence of poor parental health status, impaired fecundity or partnership breakdown, [21][22][23][24] all of which have implications for later health.…”
Section: Introductionmentioning
confidence: 99%